Primary Observation of the Causes of Temporal Hypertrophy Secondary to Fat Grafting and the Effect of Liposuction on the Hypertrophy. Issue 8 (November 2020) - Lei, Hua; Ma, Gui-e
Abstract : Objective: In Asia, the temporal hollowing is considered to be a sign of bad fortune and aging. Many people demand to correct the temporal hollowing with fat grafting. Subsequently, the temporal hypertrophy secondary to fat grafting become more and more. This study attempted to preliminarily explore the causes of temporal hypertrophy and observe the safety and effectiveness of liposuction in correcting temporal hypertrophy. Methods: A diagnostic criteria for temporal hypertrophy was established, and 55 of 78 patients who complained of temporal swelling were defined as temporal hypertrophy, and filled out a questionnaire which included patients' basic information, preoperative, intraoperative, and postoperative problems related to fat grafting, as well as their acceptance of liposuction. Analyze the results of the questionnaire to explore which factors are associated with hypertrophy. Practice liposuction on patients who are willing to try liposuction. Postoperative complications were observed to determine the safety of liposuction. The patients, doctors, and bystanders were followed up 3 months postoperative to investigate the satisfaction of the operation for analyzing the effectiveness of liposuction for temporal hypertrophy. Results: Before fat grafting, 13 (23.6%) patients without significant temporal hollowing and 42 (76.4%) patients with obvious temporal hollowing; 28 (50.9%) patients with 1 fat grafting, 20 (36.4%) with 2 fat gratings, 7 (12.7%) with 3 fat grafting. The mean time between 2 fat gratings was 4.8 months. The fat donor sites: 50 (90.9%) patients in thigh, 4 (7.3%) in abdomen, and in 1 (1.8%) in waist. The average onset time of hypertrophy in 55 patients was 13.1 months after the last fat grafting. The average onset time of temporal hypertrophy of the weight-gain group (25.7 months) was significant later than that of the weight-invariant group (7 months) ( P < 0.01). No irregularities, skin necrosis, hematoma, or infection was found in all patients. One patient showed the damage to temporal branch of facial nerve on right side, which fully recovered at 1 week postoperative. 7 (22.6%) patients, 10 (32.3%) doctors, and 8 (25.8%) laypersons reported satisfactory results; 14 (45.2%) patients, 15 (48.4%) doctors, and 14 (45.2%) laypersons reported mostly satisfactory results; 10 (32.3%) patients, 6 (19.4%) doctors, and 9 (29.0%) laypersons reported dissatisfactory results. Conclusions: To prevent temporal hypertrophy, the following points are important: to rationally choose of indication of temporal fat grafting, to wait 1 to 2 years before next fat grafting, to maintain weight stability after fat grafting, to practice conservative fat grafting, to prudently choose fat donor site. Liposuction is safe for temporal hypertrophy, but it is not easy to operate and difficult to correct all cases. Therefore, a superior treatment plan should be explored. Abstract : Supplemental Digital Content is available in the text